Sinonasal NUT carcinoma: A retrospective case series from a single institution - Wang, Lei; Zhu, Zhenzhen; Wang, Weiqing; Zha, Yang; Wang, Xiaowei; Surita, Aodeng; Liu, Yuzhuo; Lv, Wei (Frontiers in Surgery, 2023)
Purpose Nuclear protein in testis (NUT) carcinoma is a rare, aggressive tumor defined by the presence of NUT gene rearrangement. The aim of this study was to describe the clinical, radiologic, and biological features of sinonasal NUT carcinoma. Methods We retrospectively investigated NUT expression with clinicopathologic features in 145 cases with sinonasal malignancies diagnosed from January 2017 to December 2021 and reviewed the reported cases. Results Three (3/145, 2.07%) cases showed strong nuclear expression for NUT immunohistochemical, including one male and two females with ages from 37 to 57 years (mean, 45.33 years). All three cases involved the nasal cavity and sinuses; one of them involved the orbit and intracranial area. Histologically, all subjects showed poorly differentiated, small round cell morphology with distinct nuclei. All patients received surgery and chemoradiotherapy. One patient died of the disease 13 months after diagnosis, and two survived 12 and 15 months, respectively, without evidence of tumor recurrence. 51 cases of sinonasal NUT carcinoma (mean age 40.96 years) have been described to date. Among them, 28 are male, and 23 are female. Most cases expressed p63, AE1/AE3, as well as p40. Conclusion NUT carcinoma is a rare and aggressive disease with a poor prognosis. It is crucial to perform NUT rearrangement-related tests for differential diagnosis of poorly differentiated/undifferentiated tumors in the nasal cavity and sinuses.